1989
DOI: 10.2214/ajr.152.3.465
|View full text |Cite
|
Sign up to set email alerts
|

Cine-gradient-refocused MR imaging of central pulmonary emboli

Abstract: We studied the use of MR imaging with a limited-flip-angle, gradient-refocused pulse sequence to show central pulmonary emboli in I 1 patIents and to distinguish acute from chronic emboli. The central pulmonary vasculature was imaged by using a cine-limitedflip-angle (cine-MR) pulse sequence with 63/13 (TR/TE) and a 3O flip angle (8)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…With cine imaging, intraluminal clot can be distinguished from turbulent flow dephasing, by the persistence of low signal throughout the cardiac cycle. [64][65][66] Although 5 th order branches were consistently visualized in one study using cine imaging, 66 Posteraro et al 65 could not detect clot beyond the first order branches in 11 patients with pulmonary embolism.…”
Section: Pulmonary Mramentioning
confidence: 95%
See 1 more Smart Citation
“…With cine imaging, intraluminal clot can be distinguished from turbulent flow dephasing, by the persistence of low signal throughout the cardiac cycle. [64][65][66] Although 5 th order branches were consistently visualized in one study using cine imaging, 66 Posteraro et al 65 could not detect clot beyond the first order branches in 11 patients with pulmonary embolism.…”
Section: Pulmonary Mramentioning
confidence: 95%
“…Many of the studies, however, rely on a small number of patients with a high prevalence for PE. 65,67,70,72 One study 84 that directly compared CTA with pulmonary MRA, showed that pulmonary emboli were generally more easily identified on contrast enhanced CT. This was at-tributed to better spatial resolution and fewer artifacts on CTA.…”
Section: Pulmonary Mramentioning
confidence: 99%
“…6 Magnetic Resonance Imaging Currently, information on MRI evaluation of acute PE is limited, although initial reports are encouraging. 7,8 MRI may detect pulmonary emboli during imaging of the chest for other reasons.…”
Section: Cross-sectional Imagingmentioning
confidence: 99%
“…The main pulmonary artery and its primary (right and left) branches are routinely seen on standard cine images, and the technique has proved successful in diagnosing suspected emboli in these vessels (3). However, at the TE values commonly used in cine imaging, more-peripheral pulmonary vasculature is not well depicted.…”
mentioning
confidence: 99%